Interactive Vocabulary Technique in Vocabulary Mastery Teaching: A Quasi-Experimental Approach - Yuliani, Sri; Hartati, Sri; Sulaiman, Masagus; Saptika; Saputri, Kurnia (Journal of English Education, 2023)
Vocabulary is crucial in language learning. Vocabulary is also an important ability to learn to read, speak, write, and listen properly. This research aimed at figuring out whether or not the interactive vocabulary technique was effective in teaching vocabulary mastery to the Seventh-Grade Students of MTs Negeri 3 Muara Enim. Quasi experimental approach was applied in this research. This research involved 81 students of VII.1, VII.2, and VII 3 classes as the population and 54 of them as the sample regarding as control and experimental classes. Pretest and posttest were used to collect the data in line with 35 items of 17 fill-in-the- blank, 10 unscramble letters, 8 multiple choices. The data were analyzed by using Paired t-test and Independent sample t-test. The results showed that the t-obtained was 6.101 at the significant level 0.05 (5%) and t-table was 2.020 which indicated that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. It means that interactive vocabulary technique was effective in teaching vocabulary mastery to the Seventh-Grade Students of MTs Negeri 3 Muara Enim.